2022
DOI: 10.1007/s11121-022-01338-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Participant Attrition and Retention in a Perinatal Home Visiting Program

Abstract: Ethics approval: This study was reviewed and considered exempt by the Institutional Review Board at a large public university in Florida as it involved secondary data analysis (not human subjects research) and was part of a program evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…These rates are consistent with or higher than previously found reported national rates, depending on how retention was operationalized (i.e., 39.5-82.3% by 6 months; 46% by 12 months) (3,43). They were also higher than rates found by an evaluation of programs in Florida which showed retention of 62.9% six months after enrollment (44). It is important to note, however, that all previous studies on retention rates happened before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 55%
“…These rates are consistent with or higher than previously found reported national rates, depending on how retention was operationalized (i.e., 39.5-82.3% by 6 months; 46% by 12 months) (3,43). They were also higher than rates found by an evaluation of programs in Florida which showed retention of 62.9% six months after enrollment (44). It is important to note, however, that all previous studies on retention rates happened before the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 55%
“…It is encouraging that intervention feasibility, as demonstrated by high levels of parent engagement within this study, far exceeded engagement levels reported generally within home visiting interventions (42). With 80% of mothers in the sample above the clinical cut-off for classification as at high risk for child abuse potential at pre-intervention, relevance of the intervention for child welfare populations should be considered.…”
Section: Discussionmentioning
confidence: 74%